(untitled) (Global Journal of Science Frontier Research, 2020)
The relevance of the presented topic is due to the conceptual transformations of the training of masters of physical education. Currently, universities are becoming increasingly independent in developing master’s degree programs: in determining the type of program (research or practice-oriented), in choosing the type of professional activity for which students are preparing, in selecting and building content at the level of modules, disciplines, and educational material. In this regard, important issues of goals, content, and specificity of training graduate of pedagogical University, in particular, in the preparation of graduates who have no professional educational background. The study revealed the state of implementation of the master’s program in the direction of training 44.04.01 Pedagogical education, the profile "Educational technologies in the field of physical culture" in the NSPU named after K. Minin based on the analysis of academic performance and involvement in the educational process of undergraduates who have and do not have a basic education. A model of professional training of a specialist in the field of physical culture with non-core education based on the use of electronic services has also been developed.